ADOPSI TEKNOLOGI BLOCKCHAIN DI SEKTOR PUBLIK: PELUANG PEMBENTUKAN SISTEM IDENTITAS DIGITAL NASIONAL DI ERA VUCA - Suminar, Lilis Ratna; Nugroho, Alih Aji (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2023)
Digital identity is a community needs in the era of the Industrial Revolution 4.0 as it is now. The use of the E-KTP identity system in bureaucratic affairs has been considered less effective and efficient. Blockchain as a cutting-edge invention can be an alternative solution. This article aims to analyze the potential adoption of blockchain as a digital identity system. Researchers used descriptive research methods with a qualitative approach to analyze this potential. By looking at the condition of Indonesia's identity system and analyzing literature sources from international journals and articles, it can be said that it is time for Indonesia to need a new national digital identity system. The Ministry of Communication and Informatics is preparing a national digital identity system (E-KTP Digital) to manage the personal data of citizens in the digital world. This digital e-KTP has been integrated and verified with NIK. To support this security, the use of blockchain technology can be applied. The blockchain model that can be applied in the national digital identity system in Indonesia is the claim identity model proposed and described by Xiaohui Yang and Wenjie Li. The use of blockchain can increase the security and privacy of digital identities. The government needs to prepare a regulatory framework and its instruments.